2022
DOI: 10.1007/s00432-022-03922-5
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in the number of patients diagnosed with cancer during the COVID-19 pandemic in Germany

Abstract: Purpose Little is known on how coronavirus disease 2019 (COVID-19) has impacted cancer diagnosis in Germany since the first lockdown in March 2020. Therefore, this retrospective study aimed to compare the number of patients newly diagnosed with cancer in general and specialized practices in Germany between April 2020–March 2021 and April 2019–March 2020. Methods Patients aged ≥ 18 years with at least 1 visit to 1 of 1403 general and specialized practices in Germany in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
0
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 36 publications
6
20
0
6
Order By: Relevance
“…Other prominent sub-disciplines overcome the pandemic effects in the second year of observation (i.e., − 6% and + 2% for breast cancer C50; − 8% and + 1% for respiratory and thoracic cancer C30-39 ) or seem to be not affected at all (i.e., + 7% and + 3% for malignant skin cancer C43-C44; + 1% and + 2% for haemato- and lymphoid oncology C81-C96) . International findings are coherent with these developments and confirm this noxious but divergent developments (Jacob et al 2022 ; Kuzuu et al 2021 ; Monroy‐Iglesias et al 2022 ). Changes in sub-disciplines with small overall share (≤ 5% of overall oncology cases) tend to be biased by structural changes, managerial decisions, or changes in assigning out-patient physicians and practices, and display counterintuitive development (i.e., + 190% and 145% for bone and cartilage cancer C40-41, + 29% and + 25% for mesothelial cancer C45-C49).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Other prominent sub-disciplines overcome the pandemic effects in the second year of observation (i.e., − 6% and + 2% for breast cancer C50; − 8% and + 1% for respiratory and thoracic cancer C30-39 ) or seem to be not affected at all (i.e., + 7% and + 3% for malignant skin cancer C43-C44; + 1% and + 2% for haemato- and lymphoid oncology C81-C96) . International findings are coherent with these developments and confirm this noxious but divergent developments (Jacob et al 2022 ; Kuzuu et al 2021 ; Monroy‐Iglesias et al 2022 ). Changes in sub-disciplines with small overall share (≤ 5% of overall oncology cases) tend to be biased by structural changes, managerial decisions, or changes in assigning out-patient physicians and practices, and display counterintuitive development (i.e., + 190% and 145% for bone and cartilage cancer C40-41, + 29% and + 25% for mesothelial cancer C45-C49).…”
Section: Discussionsupporting
confidence: 68%
“…Oncology has widely been discussed as the medical field being particularly vulnerable to negative impact of the pandemic on the care situation (Alagoz et al 2021 ; Andrew et al 2021 ; De Luca et al 2022 ; Earnshaw et al 2020 ; Erdmann et al 2021 ; Gurney et al 2021 ; Jacob et al 2021 ; Kuzuu et al 2021 ; Patt et al 2020 ; Peacock et al 2021 ; Piontek et al 2021 ; Reichardt et al 2021 ; Ruiz-Medina et al 2021 ; Stang et al 2021 ; Tsibulak et al 2020 ; Vardhanabhuti and Ng 2021 ; Voigtländer et al 2021 ). In Germany, studies conducted in various states, e.g., Saxony (Piontek et al 2021 ), North Rhine-Westphalia (Stang et al 2021 ), or Bavaria (Voigtländer et al 2021 ), have confirmed a decline of cancer cases during different time periods of the pandemic and on national scale studies have confirmed a decrease in oncological cases in general and specialized practices in Germany for April 2020–March 2021 and March–May 2020 (Jacob et al 2021 , 2022 ). The current literature focusses on parts of the pandemic and leaves out the perspective of an in-patient oncological maximum care provider.…”
Section: Introductionmentioning
confidence: 99%
“…The most important drop was observed in the first wave, in line with previous reports from Catalan primary care 38 , 39 and elsewhere in Europe, North America, and Hong Kong. 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 The strong inverse correlation between COVID-19 workload in health care settings and cancer diagnosis reflects the sudden, overwhelming pressure on the Catalan health care system as COVID-19 cases began to skyrocket in the spring of 2020. The decline in detected cases during this wave is probably largely attributable to the temporary suspension of organized cancer screening programs and non-essential surgery, the substitution of face-to-face visits with telemedicine, and patients’ fear of going to health care facilities.…”
Section: Discussionmentioning
confidence: 99%
“…In the first pandemic wave, health systems were subjected to sudden and overwhelming pressure. 2 , 3 In cancer, this meant delaying diagnoses 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 and altering treatment regimens. 30 , 31 , 42 , 43 , 44 , 45 , 46 , 47 Subsequent pandemic waves, including the one linked to the omicron variant, have triggered new health crises.…”
Section: Introductionmentioning
confidence: 99%
“…Este descenso era esperado debido a la suspensión de programas de detección oportuna, como cáncer de seno o colon. 5 En nuestro país, la pandemia colapsó las unidades hospitalarias, pero al contar con un modelo de atención centralizada no se modificó el número de casos con leucemia aguda. Una de las explicaciones es la poca sospecha, ya que los cambios en los conteos sanguíneos (citopenias) y en las pruebas de coagulación (dimero D elevado, alargamiento de pruebas de coagulación, hipofibrinogenemia) presentes en la leucemia promielocítica pueden semejar casos severos de SARS-CoV-2, lo que dificulta la sospecha y enmascara el diagnóstico.…”
Section: Leucemia Y Covid-19 (Leucovid-19): Efecto De La Pandemia Sob...unclassified